Isolated fat pad sign in acute elbow injury: is it clinically relevant?. (June 2016) - Jie, Kim E.; van Dam, Lisette F.; Hammacher, Eric R.
Abstract : An isolated fat pad sign (i.e. joint effusion without a visible fracture), commonly seen in acute elbow injury, is associated with occult fracture and treated as such. However, the clinical relevance of an isolated fat pad is unclear, thereby questioning the need for specialized follow-up. In this study, 111 patients (median age 15 years, interquartile range 9–27 years) with an isolated fat pad sign after acute elbow injury were included. The clinical relevance of an isolated fat pad sign was derived from descriptives on pain, elbow function, treatment change, number of revisits and recovery time after 1 week follow-up and long-term follow-up. Treatment alterations were rarely made and none of the patients needed an operative intervention; also, none of the patients had persistent symptoms. The median recovery time was 3 weeks (interquartile range 2–12 weeks). This study shows that, unless symptoms persist or worsen, regular follow-up at a specialized outpatient clinic is not needed.